DISKRESI MAJELIS KEHORMATAN NOTARIS TERKAIT PERLINDUNGAN PROFESI NOTARIS DALAM PERSPEKTIF HUKUM ADMINISTRASI - HARIANTO, DANI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
The Honorary Council of Notaries is a body that has the authority to develop Notaries and has the right to give approval or rejection in matters of investigation and judicial process, especially with regard to taking photocopies of Deed Minutes and summoning Notaries to be examined in all matters relating to Notarial Deeds or Protocols made by Notaries. In Constitutional Court Decision No. 49/PUU-X/2013, the phrase